KINERJA KEPALA SEKOLAH MENENGAH ATAS BERBASIS ISLAM - Jaja Jahari (Jurnal Pendidikan Islam, 2013)
This study aims to find and analyze the factors that affect the headmaster’s performance of Islam-based senior high schools in West Java. The study is a cross-sectional research. In this study, the relationship between variables was analyzed by using statistical approach (path analysis). The testing consisted of simultanious and individual hypothesis testing with error level α = 5%. The sample was 57 schools it is the 15% of the 348 Islam-based schools as the total population that exists in West Java Province. The results showed that leadership behavior, motivation, managerial skills and compensation system are the four factors that directly or indirectly affect the headmaster’s performance of Islam-based senior high school in West Java. The degree of influence of each factor is as follows: 1) leadership was 25.6%; 2) motivation to work was 7.7%; 3) managerial capability was 22.6%, and 4) the system of compensation was 8.0%. Order of magnitude assessment of these factors is 4.17 with 90.35% degree of conformity; 4.01 with 83.34% degree of conformity; 4.34 with 92.18% degree of conformity; 3.48 with degree of conformity of 77.31%.